Teaching Model of Education Management through Google Classroom: The Trend of “The Kaizen Model” - Elihami Elihami; Ming Lin; Chang Biqing (Yayasan Keluarga Guru Mandiri, 2024)
The incorporation of technology in education, notably through platforms like Google Classroom, has prompted significant changes in teaching methods. This includes adopting the Kaizen philosophy, which prioritizes continual improvement through small steps. This article examines how this philosophy intersects with Google Classroom, highlighting its importance. This research explained the trend of “The Kaizen Model” by using bibliometrics mapping. This study aims to analyze students’ perception of the technical, process, and evaluation learning of the Teaching Model of Education Management through Google Classroom. The research method used qualitative research. The research method was a qualitative approach through VOS viewer. The object of the research was students of Philippine Women’s University who participated from various countries in the world. The instrument used questionnaires distributed via the website. The finding shows that students’ perceptions of technical indicators in the Kaizen Model learning are positive. Students’ perception of learning process indicators in the Kaizen model learning on average is positive. Students can understand the Kaizen model learning materials through discussions and communication between lecturers and students goes well. Students’ perception of evaluation indicators in the Kaizen Model learning on average are positive. The intense participation was well received by the students in the pilot courses, which allowed for improvements in areas like course ideas, course content, presentation style, and topic or detail selection. The study contributes to science for developing the concept of Kaizen through the education management department.